2000
DOI: 10.1002/1097-0231(20000815)14:15<1368::aid-rcm15>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

The significance of monoisotopic and carbon-13 isobars for the identification of a 19-component dodecapeptide library by positive ion electrospray Fourier transform ion cyclotron resonance mass spectrometry

Abstract: Harnessing the ultra high resolution capabilities of Fourier transform ion cyclotron resonance mass spectrometry (FTICR‐MS) and positive ion electrospray, we have demonstrated the significance and utility of cumulative mass defect high resolution mass separation stable isotope distribution, exact mass measurement and elemental formula as a means of simultaneously identifying 19 components of the dodecapeptide library Ac‐ANKISYQS[X]STE‐NH2. With an instrument resolution of 275 000 (average), isobaric multiplets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The number of components identified, however, decreased with increasing library size. The authors point out the difficulties they observed with increasing complexity -coalescence of peaks of similar m/z value, because of space-charge effects Ramjit and coworkers [29] of Merck Research Laboratories in West Point demonstrated the significance and utility of cumulative mass defect, stable-isotope distribution, exact mass measurement, and elemental formula as a (Fig. 5).…”
Section: Direct Fticr-ms Analysis Of Combinatorial Librariesmentioning
confidence: 99%
“…The number of components identified, however, decreased with increasing library size. The authors point out the difficulties they observed with increasing complexity -coalescence of peaks of similar m/z value, because of space-charge effects Ramjit and coworkers [29] of Merck Research Laboratories in West Point demonstrated the significance and utility of cumulative mass defect, stable-isotope distribution, exact mass measurement, and elemental formula as a (Fig. 5).…”
Section: Direct Fticr-ms Analysis Of Combinatorial Librariesmentioning
confidence: 99%
“…Ramjit et al 65 identified the components of a library containing 19 dodecapeptides simultaneously within the mass windows of 1380-1385 and 1395-1400 Da using direct infusion ultrahigh mass resolution ESI-FTICR-MS without a prior separation. Within these detection windows an average resolution of 275,000 (FWHM) was achieved, allowing the resolution of monoisotopic signals from the 13 C signals of other constituents.…”
Section: Investigation Of Compound Collections (Nonpeptides and Peptimentioning
confidence: 99%
“…The unique advantage of externally calibrated robust accurate mass measurements provided by the FTMS instruments has also received a lot of attention and it has been discussed in detail in recent comprehensive reviews [3,9]. The first small molecule FTMS applications in the pharmaceutical industry were for accurate mass measurements of pure/isolated drug candidates [10][11][12] and related degradants [13], and in the analysis of combinatorial chemistry libraries [14][15][16][17] without (or with minimal) LC separation. There are very few reports on pharmaceutical FTMS applications specifically for drug metabolism analyses and the majority of them use the advantage provided by the accurate mass measurements to *Address correspondence to this author at the Bristol-Myers Squibb PRI, Mail Stop L14-09, PO Box 4000, Princeton, NJ 08543-4000, USA; Tel: (609) 252 5722; E-mail: mark.sanders@bms.com confirm/elucidate structures for parent drug molecules and corresponding metabolites [12,18].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous examples in the literature for on-line low-flow (< 0.1 mL/min) LC-FTMS for both proteomic [23][24][25][26][27] and small molecule studies [15,28]; however, for traditional small molecule analyses where flow rates typically vary between 0.2 -1 mL/min, there are few reports [29]. The big step forward for drug metabolism analyses and small molecules analyses in general came with the introduction of the hybrid FTMS instruments, including the quadrupole FTMS from Bruker Daltonics (Billerica, MA) and IonSpec (Lake Forest, CA) and the linear ion trap FTMS (LTQ-FT) from Thermo Electron (San Jose, CA).…”
Section: Introductionmentioning
confidence: 99%